Microorganismo eficientes (EM), en la elaboración de compost a partir del raquis y pseudo tallo de banano (Mussa spp.) - Goya Muentes, Edison Eloy (2013)
This research work was carried out in the province of Los Rios, Canton Valencia, Valencia Parish, in the fincaRobertita. Its coordinates are cartographic whose geographic coordinates are South latitude 1 º, 25 ', 0 '; West longitude 79 º, 35 ', or" altitude 120 meters above sea level, the treatments for this investigation are set out in correspondence to the rate of application of the microorganisms in the efficient waste that are obtained from the harvest of a hectare of banana. T1 = 1.5 Liters of EM in 1 tonne of waste T2= 2 liters of EM in 1 tonne of waste T3= 2.5 liters of EM in 1 tonne of waste The result in the obtaining of composting with the application of effective microorganisms (lactic acid and yeast, Actinomycetes) According to the analysis of variance applied to the averages of the treatments of the relations Ca/Ca/Mg, Mg and Ca+C/N and K+Ca+Mg and calculated sum of bases in the composition of organisms snowmobile (Em) we show that proved to be not significant for all of them, with coefficients of variation of 7.57 %, 3.77 % 13.66 % and 3.60 % respectively. Chemical analysis shows that the largest concentration of organic matter is presented in the composting the highest percentage is T3, 28.85 % and lower percentage T2 with a value of 19.65 %; the average of the; Moisture the highest percentage is of T2 and T3, 41.73 % and lower percentage T3 with a value of 41.56 %.